The Role of Professional Mission in Buffering Secondary Traumatization. - Sasson-Shoshan, Tali; Schorr, Adi Vitman; Govrin-Yehudain, Yoad; Klugerman, Dana; Cohen, Shahaf; Yehuda, Ira; Abas, Fatma; Ayal, Maytal; Chiko, Sivan; Lev-Wiesel, Rachel (Social Work, 2026)
The Hamas massacre on October 7, 2023, resulted in approximately 1,400 civilian deaths and escalated into a war between Israel and its neighbors. This conflict had a profound impact on healthcare professionals, including social workers, who faced the dual burden of addressing the needs of others while managing their own trauma. This study examined the role of personal resources and professional mission in preserving the well-being of 116 Israeli social workers operating within a war-related shared reality. Participants were recruited from three regions with differing levels of exposure: Northern Israel (relocated due to rocket attacks), Southern Israel (directly affected by the massacre and ongoing rocket fire), and Central Israel (exposed to repeated rocket alarms). Self-report questionnaires assessing psychological distress, potency, professional mission, and work-to-family conflict were administered. Findings indicated that potency and professional mission emerged as key differentiating variables in the decision tree model, highlighting their central role in shaping psychological distress outcomes during wartime. In contrast, demographic variables and family-to-work conflict served as significant predictors of psychological distress. These findings underscore the importance of internal and professional resources in mitigating psychological distress among social workers facing a war-related shared reality.